Synthesis and Characterization of Zinc Oxide Nanostructures for Photocatalytic Applications - Mansor, Nur Nabilah; Ameruddin, Amira Saryati (Enhanced Knowledge in Sciences and Technology, 2025)
Zinc oxide has been widely investigated by many researchers due to their potential in an optoelectronic device. The problem statement focuses on the need for effective synthesis techniques using the co-precipitation method. This method aims to facilitate exact control of the size, shape, and morphology of ZnO nanostructures to improve and optimise their photocatalytic characteristics. The study aimed to synthesise ZnO nanoparticles by the co-precipitation technique and to examine the properties of ZnO nanoparticles under varying reaction concentrations and pH levels. Multiple methods exist for the synthesis of ZnO nanoparticles. This study focused on the co-precipitation synthesis process. The characterisation of ZnO nanoparticles was conducted using Field Emission Scanning Electron Microscopy (FESEM), X-ray Diffraction (XRD), and Ultraviolet-Visible Spectrophotometry (UV-Vis) to investigate the morphological characteristics of ZnO nanoparticles at varying reaction concentrations and pH levels. The optical and structural properties of the synthesized ZnO products have been evaluated. The nanorods that were grown were found to exhibit good optical properties. This method is environmentally friendly, cost-effective, and simple, making it a potential approach for large-scale production of devices and other applications.